2002
DOI: 10.1034/j.1399-3054.2002.1160404.x
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between exogenous glycine betaine and the photorespiratory pathway in canola leaf discs

Abstract: The uptake and accumulation of exogenously supplied glycine betaine (GB) by canola (which never accumulates GB in response to stress) leaf discs has been found to induce damage to some of their structural and functional components. As a consequence some free amino acids were accumulated, particularly glutamine and glycine. Similar results were obtained with leaf discs of Arabidopsis thaliana i.e. another cruciferous plant that does not naturally produce significant amounts of GB. In contrast no changes in glut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…For example, Larher et al (1995) found that exogenous GB exerts inhibitory effects on osmo-induced proline accumulation in rape leaf discs suggesting that it is not a compatible solute. In contrast, Sulpice et al (2002) found an increase in leaf proline concentration in response to exogenous GB application in canola leaf discs. The difference between the results of the present experiment and those of the above mentioned studies can be explained by the fact that in the present study, GB was sprayed on intact plants, whereas contradictory results of some pervious studies (Larher et al 1995;Sulpice et al 2002) were based on indirect evidence (in vitro).…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…For example, Larher et al (1995) found that exogenous GB exerts inhibitory effects on osmo-induced proline accumulation in rape leaf discs suggesting that it is not a compatible solute. In contrast, Sulpice et al (2002) found an increase in leaf proline concentration in response to exogenous GB application in canola leaf discs. The difference between the results of the present experiment and those of the above mentioned studies can be explained by the fact that in the present study, GB was sprayed on intact plants, whereas contradictory results of some pervious studies (Larher et al 1995;Sulpice et al 2002) were based on indirect evidence (in vitro).…”
Section: Discussionmentioning
confidence: 60%
“…The present findings clearly showed nonsignificant effects of exogenous pre-sowing or foliar application of GB on total free amino acids in sunflower plants grown under both normally irrigated and drought stressed regimes. In contrast, Sulpice et al (2002) reported a marked increase (2-to 3-fold) in free amino acids by exogenous application of GB on detached leaf discs of Arabidopsis thaliana and Brassica napus.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Yang and Lu (2006) concluded that if endogenous level of GB reaches a threshold level due to either foliar application of high concentrations of GB or by increasing the number of foliar applications of effective concentration, or applied through the rooting medium for a longer duration even at low concentration, it does not act as an osmoregulator substances, thereby causing phytotoxicity. In this respect, Sulpice et al (2002) found that enhanced endogenous GB due to exogenous GB application at high doses caused the damaging effects in Brassica napus. Kotb and Mansour (2012) concluded that GB acted as osmoregulating substance and enhanced water stress tolerance of maize plant when applied at a level of 15 mM , whereas, 20 mM GB decreased growth and yield of maize.…”
Section: Effective Doses Of Gbmentioning
confidence: 99%
“…It might also result from their noncompatibility in transgenic types. Compatibility of these substances seems indeed to be restricted to the wild genotypes that naturally produce them (Gibon et al, 1997;Romero et al, 1997;Sulpice et al, 1998Sulpice et al, , 2002Bohnert and Shen, 1999;Hare et al, 2002).…”
mentioning
confidence: 99%